যদি \(\cfrac{x}{y+z}=\cfrac{y}{z+x}=\cfrac{z}{x+y}\) হয়, তবে দেখাও যে, প্রতিটি অনুপাতের মান হয় \(\cfrac{1}{2}\) না হয় -1 Madhyamik 2015


ধরি, \(\cfrac{x}{y+z}=\cfrac{y}{z+x}=\cfrac{z}{x+y}=k\)

[\(k\) একটি অশূন্য ধ্রুবক ]


সুতরাং, \(x=k(y+z), y=k(z+x)\) এবং \( z=k(x+y)\)
\(\therefore x+y+z=k(y+z)+k(z+x)+k(x+y)\)
বা, \(x+y+z=k(y+z+z+x+x+y)\)
বা, \(x+y+z=2k(x+y+z)\)
বা, \((x+y+z)-2k(x+y+z)=0\)
বা, \((x+y+z)(1-2k)=0\)

\(\therefore \) হয়, \(x+y+z=0\)
নয়, \(1-2k=0\) বা, \(-2k=-1\) \(\therefore k=\cfrac{1}{2}\)
\(\therefore \) প্রত্যেকটি অনুপাতের মান হয় \(\cfrac{1}{2}\)

আবার, \(x+y+z=0\) হলে \(y+z=-x\)
\(\therefore\cfrac{x}{y+z}=\cfrac{x}{-x}=-1\)
আবার, \(z+x=-y\)
\(\therefore\cfrac{y}{z+x}=\cfrac{y}{-y}=-1\)
এবং,\(x+y=-z\)
\(\therefore\cfrac{z}{x+y}=\cfrac{z}{-z}=-1\)

\(\therefore\cfrac{x}{y+z}=\cfrac{y}{z+x}=\cfrac{z}{x+y}\) হলে প্রত্যেকটি অনুপাতের মান হয় \(\cfrac{1}{2}\) অথবা \(-1\) (প্রমাণিত)

Similar Questions